What is public agency strategic analysis (PASA) and how does it differ from public policy analysis and firm strategy analysis? - Aidan R. Vining (Administrative Sciences, 2016)
Public agency strategic analysis (PASA) is different from public policy analysis because public agency executives face numerous constraints that those performing "unconstrained" policy analysis do not. It is also different from private sector strategic analysis. But because of similar constraints and realities, some generic and private sector strategic analysis techniques can be useful to those carrying out PASA, if appropriately modified. Analysis of the external agency environment (external forces) and internal value creation processes ("value chains", "modular assembly" processes or "multi-sided intermediation platforms") are the most important components of PASA. Also, agency executives must focus on feasible alternatives. In sum, PASA must be practical. But public executives need to take seriously public value, and specifically social efficiency, when engaging in PASA. Unless they do so, their strategic analyses will not have normative legitimacy because enhancing public value is not the same as in some versions of public value or in agency "profit maximization". Although similarly constrained, normatively appropriate public agency strategic analysis is not "giving clients what they want" or "making the public sector business case". PASA must be both practical and principled.
Keywords: 350; public agency; strategic analysis; external environment; resources; value creation; social efficiency; public value; value chain; modular assembly; multi-sided platform